2020
DOI: 10.3390/biom10071058
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Empowered FTIR Spectroscopy Serum Analysis Stratifies Healthy, Allergic, and SIT-Treated Mice and Humans

Abstract: The unabated global increase of allergic patients leads to an unmet need for rapid and inexpensive tools for the diagnosis of allergies and for monitoring the outcome of allergen-specific immunotherapy (SIT). In this proof-of-concept study, we investigated the potential of Fourier-Transform Infrared (FTIR) spectroscopy, a high-resolution and cost-efficient biophotonic method with high throughput capacities, to detect characteristic alterations in serum samples of healthy, allergic, and SIT-treated mice and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…30,79,8184 and can result in better classification models afterwards. 72,8593 Since derivation enhances the noise level of spectra, it is only advisable to use on high S/N data.…”
Section: Resultsmentioning
confidence: 99%
“…30,79,8184 and can result in better classification models afterwards. 72,8593 Since derivation enhances the noise level of spectra, it is only advisable to use on high S/N data.…”
Section: Resultsmentioning
confidence: 99%
“…Their classification models of the FTIR spectra of human sera generated using deep learning showed an overall accuracy of 93.9%. Furthermore, the model they established successfully discriminated against allergy, allergen-specific immunotherapy, and healthy individuals with true positive rates of 93.3, 91.7, and 96.7%, respectively [44]. Another FTIR study classifying inflammatory fibrous hyperplasia (IFH) lesions and normal oral mucosa (NM) using the PCA-LDA approach had a sensitivity and specificity of 87.5 and 100%, respectively [69].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the application of ATR-FTIR combined with a neural network could differentiate between sera from healthy subjects and from breast cancer patients with a sensitivity of 92-95% and specificity of 95-100% [43]. Another finding reported the possibility of ATR-FTIR coupled with deep learning to be applied for stratifying healthy, allergic, and allergen-specific immuno-therapy in mice and humans [44]. Unfortunately, to the best of our knowledge, ATR-FTIR empowered with machine learning algorithms has not been widely applied to investigate immunosenescence.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, some researchers have used a combination of FTIR spectroscopy and ML to propose a new strategy for canine visceral leishmaniasis diagnosis . Similarly, researchers demonstrated the potential of this approach to quickly diagnose clinical therapeutic monitoring in patients with allergies . Many studies have shown that using FTIR spectroscopy combined with ML has great clinical potential. …”
mentioning
confidence: 99%